2015
DOI: 10.5539/jfr.v4n5p172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tiger Nut Residue Flour Inclusion on the Baking Quality of Confectionaries

Abstract: Cakes and biscuits were prepared from blends of wheat and tiger nut residue flours produced using raw and dry extraction method and substituted at 5%, 10%, 15% and 20% levels. The cakes and biscuits were analyzed for proximate composition, physical characteristics and sensory properties. Results for proximate composition indicated that moisture, fibre, ash, protein and fat contents increased with an increase in tiger nut residue substitution. Ash content for cake increased from 0.93% in sample A (100% wheat fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…This involves incorporation of food materials that are rich in nutrient such as fibre, protein, minerals and vitamins with wheat flour, a process called composite flour technology. Several studies have been carried out on the chemical and physical properties of various flours blended with wheat flour and this showed that composite flours produced from cereals, tubers, fruits, legumes and nuts are preferable and have an advantage of enhancing the overall nutrition and sensorial properties of the finished product than products produced from single wheat flour [4][5][6][7][8]. However, the selection of components to be used in composite blends depends on the availability and nutritional potentials of the raw materials [2].…”
Section: Introductionmentioning
confidence: 99%
“…This involves incorporation of food materials that are rich in nutrient such as fibre, protein, minerals and vitamins with wheat flour, a process called composite flour technology. Several studies have been carried out on the chemical and physical properties of various flours blended with wheat flour and this showed that composite flours produced from cereals, tubers, fruits, legumes and nuts are preferable and have an advantage of enhancing the overall nutrition and sensorial properties of the finished product than products produced from single wheat flour [4][5][6][7][8]. However, the selection of components to be used in composite blends depends on the availability and nutritional potentials of the raw materials [2].…”
Section: Introductionmentioning
confidence: 99%